An Hybrid Power Control Method For Femto Cells To Mitigate Interference Caused By Macro Cells - Singh, Sukhpreet (My University, 2018)
The rise of new information and video services combined with an expansion in the quantity of user devices, for example, advanced cell-phones, tablets and laptops etc. has constrained mobile operating companies to inspect new ideas for expanding coverage issue, boosting datatransmission and reception rates and bringing down capital and maintenance expenditure of their mobile network. An effective method to manage these requests is the idea of Small Cell Networks (SCN). Smaller-cells have a solid potential for expanding the network coverage, efficiency and system limit of next generation mobile systems while then again the deployment costs for the network service provider is kept in to a very low level. This work is centered on effective power control in Small-Cell-Networks. Specifically, we propose a power control method for proficient power allocating in small cell networks especially the femto cells in Small cell networks. The suggested method effectively controls system-frameworks' interference along with insuring quality of service to macro users. We present the strategy of Priority based Grouping which uses one algorithm at a time among three power allocating algorithms in which first algorithm uses Fixed HeNB power setting ,second algorithm uses smart power control based on interference measurement from macro NodeB and third uses HeNB power control based on HeNB-MUE path loss, in which home clients in the topology is allocated to one of the accessible groups with different target throughput requirements as far as power necessities and to deliver the required trafficking load of the network. The system effectively refreshes the Home developed Node B (Femto node) power control setting in the favor of the effective use of the topology of the macro as well as home clients simultaneously in real time scenario. Furthermore, contingent upon the analyzed activity situation the system can give better insurance (regarding impedance) either on full scale clients or on home clients. Proposed algorithm is tested on a simulated traffic scenario in which 9 macro and 7 femto cells are simulated with 219 MUEs, 51 initial HUEs gradually distributed in time domain in which femto users (Hue) are further increased to 821 in which 770 are inserted during simulation as the iterations rises. MUE population remains constant in the simulation. It has been observed that algorithm four chosses algorithm three when femto cell is on the boundary of the macro cells, as there is least interference to the macro cell center in which little power is efficient to achieve the target throughput. When femto cell is near to center, it uses algorithm one in group 3 as it needs smaller throughput target means less power so that least interference is achieved with that of macro cell users and algorithm three is used for the first and second group as more throughput was required.
Keywords: femto cell; LTE; Macro cell; interference; power control